2008
DOI: 10.1038/sj.bjc.6604528
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo chemosensitivity testing and gene expression profiling predict response towards adjuvant gemcitabine treatment in pancreatic cancer

Abstract: Efficacy of chemotherapy for pancreatic cancer may be improved by tailoring it to individual chemosensitivity profiles. Identification of nonresponders before initiation of treatment may help to avoid side effects. In this study, primary pancreatic cancer cells were isolated from 18 patients undergoing pancreaticoduodenectomy for pancreatic cancer. Eight commonly used pancreatic cancer cell lines were used as controls. Ex vivo chemosensitivity for gemcitabine, 5-fluorouracil, mitomycin-C, cisplatinum, oxalipla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 29 publications
0
35
0
3
Order By: Relevance
“…A number of chemosensitivity assays were developed over the last decades to predict the responsiveness of tumors to chemotherapy [19][20][21] . In recent years, the ATP-TCA method is a novel approach to test chemosensitivity in solid tumors [22][23][24][25][26] .…”
Section: Discussionmentioning
confidence: 99%
“…A number of chemosensitivity assays were developed over the last decades to predict the responsiveness of tumors to chemotherapy [19][20][21] . In recent years, the ATP-TCA method is a novel approach to test chemosensitivity in solid tumors [22][23][24][25][26] .…”
Section: Discussionmentioning
confidence: 99%
“…Characterization of PC cell lines has proven especially useful in providing new insights into phenotypic changes associated with gemcitabine resistance. 26 Although this approach has identified a number of genes likely to be involved in the development of chemoresistance ( Fig. 1), their clinical impact remains controversial.…”
Section: Chemoresistance and Chemosensitivity In Pancreatic Cancermentioning
confidence: 99%
“…Acquired resistance toward gemcitabine might partially be mediated by upregulation of the apoptosis inhibitors Bcl-2, Bcl-xL, Mcl-1, survivin and the cellular inhibitor of apoptosis protein-1 (cIAP-1). 10,11,[26][27][28] The proapoptotic proteins BNIP3 and Bax related to apoptosis induction in gemcitabine-resistant cell lines with a significant tumor regression. Erkan et al and Akada et al showed that silencing of BNIP3 by small interfering RNA (siRNA) correlated with increased chemoresistance.…”
Section: Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…These are characterized by tumor desmoplasia, early local extension to contiguous structures, metastases to regional lymph nodes and to the liver (2)(3)(4). Moreover, pancreatic cancer cells are usually resistant to the programmed cell death (apoptosis) mediated by conventional chemotherapeutic agents (5,6). It is generally believed that cancer cells have an altered cellular physiology characterized by abundance of growth signals, insensitivity to cycle arrest signals, and evasion of apoptosis (7).…”
Section: Introductionmentioning
confidence: 99%